4(x-5)=5x-25

Simple and best practice solution for 4(x-5)=5x-25 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(x-5)=5x-25 equation:


Simplifying
4(x + -5) = 5x + -25

Reorder the terms:
4(-5 + x) = 5x + -25
(-5 * 4 + x * 4) = 5x + -25
(-20 + 4x) = 5x + -25

Reorder the terms:
-20 + 4x = -25 + 5x

Solving
-20 + 4x = -25 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
-20 + 4x + -5x = -25 + 5x + -5x

Combine like terms: 4x + -5x = -1x
-20 + -1x = -25 + 5x + -5x

Combine like terms: 5x + -5x = 0
-20 + -1x = -25 + 0
-20 + -1x = -25

Add '20' to each side of the equation.
-20 + 20 + -1x = -25 + 20

Combine like terms: -20 + 20 = 0
0 + -1x = -25 + 20
-1x = -25 + 20

Combine like terms: -25 + 20 = -5
-1x = -5

Divide each side by '-1'.
x = 5

Simplifying
x = 5

See similar equations:

| -21-c=10 | | -9b=8 | | -123=-23-20y | | 103=30x+13 | | 24+11y=112 | | 61-2x=7-6x | | 1.8q-10.1q+1.3=-65.1 | | -2*sin(x)-2*cos(x)=0 | | -2sin(x)-2cos(x)=0 | | -6x+7+7x-3=-5x+6x+7 | | x+1.6=9.5 | | 3c-2b-(3b-c)= | | -x^2-4x-13=0 | | -3x+4=4-3x | | 4a+4b-5c= | | -7x^2-91x-294=0 | | 3x+49=94 | | 1.46e+299=0 | | 1.46e-6=0 | | 5*5-2=23 | | 5*5/8 | | 8-x=4-5(2+x) | | 8x^3+9x^2-6x-7=0 | | 0.092(0.94)= | | 8-(1/6)x^2-(1/3)x=0 | | 6/7x-2/7=5 | | Cos(6x)+3cos(3x)=1 | | 8-1/6x^2-1/3x=0 | | -7/8s=-6/7 | | 2*ln(2)-2=x | | 5x-15=2x+15 | | y=8+4x-x^2 |

Equations solver categories